Global Pentecostal movements : migration, mission, and public religion - Wilkinson, Michael, 1965- (International Studies in Religion and Society, 2012)
This volume contributes to the growing body of literature on religion and globalization and specifically global Pentecostal movements. While Pentecostalism worldwide shares a cultural resemblance, it is also localized and expressed in different ways. The variety of Pentecostalisms throughout the world are illustrated through important themes of mission, migration, and public religion. The global flows of Pentecostal practices, beliefs, and cultures, brings into contrast these variations. Negotiating what it means to be Pentecostal often leads to conflict and questions of identity. Interaction with other religions like Islam in Africa, mission work in Asia, and migration to Europe and North America is problematized. Regional coverage includes Africa, Asia, Latin America, Europe, and North America.